1984
DOI: 10.1002/chin.198422320
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ISOLATION AND STRUCTURE ELUCIDATION OF NEAPOLITANOSE (O‐β‐D‐GLUCOPYRANOSYL‐(1 → 2)‐O‐(β‐D‐GLUCOPYRANOSYL‐(1 → 6))‐D‐GLUCOSE), A NEW TRISACCHARIDE FROM THE STIGMAS OF GARDEN CROCUSSES (CROCUS NEAPOLITANUS VAR.)

Abstract: Aus der Titelpflanze werden die Carotinoide (I) isoliert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In cell suspension cultures of C. sativus a crocetin with two trisaccharide molecules has been identified, two O -β- D -glucopyranosyl-(1→2)- O -[β- D -glucopyranosyl-(1→6)]- D -glucose groups are present at each end of the molecule ( Dufresne et al, 1997 ), but this crocin has never been reported in the plant. This type of crocin with six glucose molecules, was also identified in Crocus neapolitanus , and accordingly the trisaccharide structure designated as neapolitanose ( Rychener et al, 1983 ). Crocin-3 has six glucose molecules and its retention time and spectral data suggest that crocin-3 is a crocetin neapolitanosyl di-ester.…”
Section: Discussionmentioning
confidence: 91%
“…In cell suspension cultures of C. sativus a crocetin with two trisaccharide molecules has been identified, two O -β- D -glucopyranosyl-(1→2)- O -[β- D -glucopyranosyl-(1→6)]- D -glucose groups are present at each end of the molecule ( Dufresne et al, 1997 ), but this crocin has never been reported in the plant. This type of crocin with six glucose molecules, was also identified in Crocus neapolitanus , and accordingly the trisaccharide structure designated as neapolitanose ( Rychener et al, 1983 ). Crocin-3 has six glucose molecules and its retention time and spectral data suggest that crocin-3 is a crocetin neapolitanosyl di-ester.…”
Section: Discussionmentioning
confidence: 91%
“…The crocins pattern of several autumn Crocus stigmas had been analysed previously [16], but only one study has been performed on one spring-flowering species [44]. The detection of crocins with different glucosylation profiles in the tepals of these species, prompted us to determine whether crocins follow a similar pattern in the stigma tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Dufresne et al (1999) in experiments with C. sativus cell suspensions supplemented with crocetin detected the presence of more-polar crocetin glucosides as major products, which were not detected in stigma tissue. However, crocetin glucosides with more glucose molecules than those detected in C. sativus stigmas have been found in Crocus neapolitanus stigmas (Rychener et al 1984), suggesting that in planta the GTase enzyme is able to form long glucose chains attached to the crocetin molecule, similar in length and complexity to the crocetin glucosyl esters regulated by other enzyme activities, such as degrading enzymes.…”
Section: Discussionmentioning
confidence: 97%